Perancangan Kalkulator Elemen Mesin untuk Perencanaan Poros - Suryanto, Hendri; Herraprastanti, Eva Hertnacahyani; Wahyusari, Retno; Gunawan, Helmi (Politeknik Negeri Padang, 2025)
To design a transmission shaft requires quite complicated calculations, the calculation time is also quite long and the calculations must be careful because they are done manually, as has been done so far. The calculation results must also be accurate because the size of the shaft that does not meet the requirements can result in failure. To meet these needs, calculations in shaft design can be done with a tool, namely a software application that is run on a computer. The purpose of this study is to produce a software application or machine element calculator for shaft planning using the Matlab GUI, and to increase the efficiency of shaft planning in terms of time. This machine element calculator is designed by selecting the Matlab GUI menus according to the calculation formulas for the torsional load shaft diameter, namely Edit Text, Static Text, Panel and Push Button. Then arrange and edit the GUI menus through the Property Inspector and create a program (Matlab Code) for calculating the shaft diameter through the Callback menu. With this calculator, calculations in transmission shaft planning can be accelerated, which is an average of 24.8 minutes faster than manual calculations, which is an average of 34.8 minutes.